2022
DOI: 10.1212/wnl.0000000000200546
|View full text |Cite
|
Sign up to set email alerts
|

Association of Ambient Particulate Matter Pollution of Different Sizes With In-Hospital Case Fatality Among Stroke Patients in China

Abstract: Objective:To characterize the association of ambient particulate matter (PM) pollution of different sizes (particulate matter ≤1 µm in aerodynamic diameter [PM1], PM2.5, and PM10) with in-hospital case fatality among stroke patients in China.Methods:We collected hospitalizations due to stroke in four provinces in China from 2013 to 2019. Seven-day and annual averages of PM prior to hospitalization were estimated using bilinear interpolation and residential addresses. Associations with in-hospital case fatality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 47 publications
1
20
0
Order By: Relevance
“…Public holidays (PHs) and days of the week (DOW) were adjusted for as dummy variables in the models. Temporal trends, daily mean temperature, and relative humidity were controlled for as natural cubic splines ( 28 ). Degree of freedom (df) was selected by referring to Akaike Information Criterion (AIC), and we chose 5 df per year for temporal trends and 3 df for the daily mean temperature and relative humidity.…”
Section: Methodsmentioning
confidence: 99%
“…Public holidays (PHs) and days of the week (DOW) were adjusted for as dummy variables in the models. Temporal trends, daily mean temperature, and relative humidity were controlled for as natural cubic splines ( 28 ). Degree of freedom (df) was selected by referring to Akaike Information Criterion (AIC), and we chose 5 df per year for temporal trends and 3 df for the daily mean temperature and relative humidity.…”
Section: Methodsmentioning
confidence: 99%
“…Strong associations and negative effects between ambient gaseous pollution (e.g., NO2, SO2, and CO) and a variety of diseases has been demonstrated for people of all ages through multiregional and national cohort studies in China. These diseases include general mortality , cause-specific cardiovascular disease (Xu et al, 2022a), ischemic and hemorrhagic stroke (Xu et al, 2022b;Wu et al, 2022b;Cai et al, 2022;He et al, 2022), dementia mortality (Liu et al, 2022), blood pressure (Song et al, 2022;Wu et al, 2022a), renal function (Li et al, 2022a), neurodevelopmental delay (Su et al, 2022), serum liver enzymes , overweight and obesity , insomnia (Xu et al, 2021), subjective sleep quality (Wang et al, 2022), and visual impairment (Chen et al, 2022a). These studies attest well to the value of the CHAP dataset with some unique merits for the sake of public health, among others, now and in the future.…”
Section: Successful Applicationsmentioning
confidence: 99%
“…It has been well documented that air pollution is associated with morbidity and mortality of stroke and cardiovascular diseases [7][8][9][10] ; limited information exists about the effect of air pollution on the clinical trajectory of stroke. A retrospective cohort study of 96,582 adults from Kaiser Permanente Northern California reported significant associations between particle pollution and poststroke cardiovascular mortality among adults with a history of stroke.…”
mentioning
confidence: 99%